SUPERHYDROPHOBIC AND ANTIBACTERIAL COATINGS ON VARIOUS COTTON FABRICS USING ZNO AND AESO - Wijaya, Hastono; Gapsari, Femiana; Sulaiman, Abdul M.; Harmayanti, Afifah; Barasa, Alvadro; Andrean, Janu; Warman, Sa Bashkaran Adi; Kriswardhana, Willy; Naimah, Azimatun (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Superhydrophobic coatings on cotton utilized in medical applications like hospital gowns and bed linens to offer a protective barrier against fluids and bacteria. Masks were worn with different types of materials. In this study, various cotton employed ZnO and AESO to effectively decrease the surface energy of cotton fabric via a Schiff base reaction. This chemical transformation resulted in the formation of a textured surface structure that exhibited robust adhesion qualities. The study demonstrates that the superhydrophobic coating on silk fabric increases 153. 59%. The coating on silk provides a reference for fabric types with ZnO and AESO coatings.